Influence of UGT2B7, OPRM1 and ABCB1 Gene Polymorphisms on Postoperative Morphine Consumption. (19th May 2014) - Bastami, Salumeh; Gupta, Anil; Zackrisson, Anna‐Lena; Ahlner, Johan; Osman, Abdimajid; Uppugunduri, Srinivas
Abstract Therapeutic modulation of pain with morphine and other opioids is associated with significant variation in both effects and adverse effects in individual patients. Many factors including gene polymorphisms have been shown to contribute to the interindividual variability in the response to opioids. The aim of this study was to investigate the significance of UGT2B7, OPRM1 and ABCB1 polymorphisms for interindividual variability in morphine‐induced analgesia in patients undergoing hysterectomy. The frequency of these polymorphisms was also investigated in forensic autopsies as morphine is also a very commonly abused drug. Blood samples were collected from 40 patients following abdominal hysterectomy, 24 hr after initiation of analgesia through a patient‐controlled analgesia (PCA) pump. Samples were genotyped and analysed for morphine and its metabolites. We also genotyped approximately 200 autopsies found positive for morphine in routine forensic analysis. Patients homozygous for UGT2B7 802C needed significantly lower dose of morphine for pain relief. The same trend was observed for patients homozygous for ABCB1 1236T and 3435T, as well as to OPRM1 118A. The dose of morphine in patients included in this study was significantly related to variation in UGT2B7 T802C. Age was significantly related to both dose and concentration of morphine in blood. Regression analysis showed that 30% of differences in variation in morphine dose could be explained by SNPs in these genes. The genotype distribution was similar between the forensic cases and the patients. However, the mean concentration of morphine was higher in forensic cases compared to patients. We conclude that gene polymorphisms contribute significantly to the variation in morphine concentrations observed in individual patients.